Ef fect of Laser Radiation in Seeds on Germination and Yield of Peanuts in the Field (Arachis hypogaea L.) (TERRA LATINOAMERICANA, 2025)
Peanut is a leguminous plant that, in addition to having positive ef fects on soil quality, provides oilseeds, which have multiple uses, because they are nutritious, medicinal, and economically important. Currently, various studies are focused on increasing the content of antioxidant compounds, as well as improving the productivity and quality of crops, with the aim of developing higher quality ingredients and functional foods. In this sense, the objective of this study was to evaluate the ef fects of laser radiation on peanut seeds on agronomic parameters of the crop under field conditions. The  experiment  was  established  under  field conditions in the town of Nicolás Bravo, belonging to the municipality of Chiapa de Corzo, Chiapas. The seeds were irradiated with a motorized red laser bar of the steelpro® brand, with a wavelength of 636 nm and an intensity of 120 mW. The exposure time of seeds to the red laser was 15 minutes and non-irradiated seeds were used as a control. Each experimental unit consisted of 100 seeds with six replicates. Germination percentage, agronomic characteristics of peanuts and pod yield were evaluated. The results show that laser radiation applied to seeds before sowing has positive ef fects on the agronomic characteristics of pods and seeds such as: the increase in the number of pods and seeds per plant, the dry weight of both components, as well as the yield of pods harvested under field conditions. Therefore, laser radiation applied to seeds is a biotechnological alternative to increase peanut production. It is suggested that further studies be carried out on the harvested seeds to determine if there are changes or improvements in the nutritional quality of the seeds.
Keywords: physical biostimulation; agronomic characteristics; pod yield